Polymorphism of the Lipoprotein Lipase Gene and Risk of Atherothrombotic Cerebral Infarction in the Japanese - Shimo-Nakanishi, Yumi; Urabe, Takao; Hattori, Nobutaka; Watanabe, Yoshiro; Nagao, Takehiko; Yokochi, Masayuki; Hamamoto, Makoto; Mizuno, Yoshikuni (Stroke (1970), 2001)
Background and Purpose —Lipid and lipoprotein abnormalities have been implicated in the pathogenesis of ischemic cerebrovascular disease and atherosclerosis. Lipoprotein lipase (LPL) plays an important role in plasma lipoprotein metabolism. Several studies have recently reported the presence of a relationship between Ser447Stop mutation of LPL and coronary artery disease. Other polymorphisms ( Hin dIII and Pvu II) of the LPL gene have already been shown to correlate significantly with dyslipidemia. We investigated whether these polymorphisms are associated with increased risk of ischemic cerebrovascular disease (CVD). Methods —We recruited 177 CVD patients (atherothrombotic infarction, n=71; cardioembolic infarction, n=30; lacunar infarction, n=76) and 177 healthy control subjects. Subjects were genotyped for the Ser447Stop mutation and for Hin dIII/ Pvu II restriction fragment length polymorphisms of the LPL gene, and the findings were investigated for associations with the clinical subtypes of CVD and with lipid levels. Results —The Ser447Stop mutation correlated significantly with CVD (0.107 versus 0.158; P =0.035). For the CG+GG versus CC genotype, the odds ratio between control subjects and CVD patients with atherothrombotic infarction was 0.42 (95% CI, 0.18 to 0.99) ( P =0.046). Serum HDL cholesterol and triglyceride levels did not correlate significantly with the Ser447Stop genotype. Hin dIII polymorphism correlated significantly with CVD (0.234 versus 0.169; P =0.031), but the frequency of Pvu II polymorphism was not significantly different between groups. Conclusions —Our results suggest that the Ser447Stop mutation of the LPL gene is a novel genetic marker for low risk of atherothrombotic cerebral infarction.